Government-led Resettlement after Natural Disasters as a Durable Solution? The Case of Cyclone Idai. (25th December 2020) - Jacobs, Carolien; Almeida, Bernardo
Abstract: Thousands of people had to flee their homes when Cyclone Idai hit Mozambique in 2019. In its aftermath, the government resettled more than 80, 000 people from high-risk areas to safer ground. This article analyses resettlement as a durable solution to disaster response. The question of durable resettlement due to climate-related displacement is especially pertinent in the light of ongoing climate change. Based on empirical research, we show that, although the government succeeded in providing a short-term response to the disaster, there are two major impediments to using resettlement as a durable solution: the lack of citizen participation in the decision-making process leading to resettlement; and the gap between the short-term humanitarian perspective and a longer-term development viewpoint. Resettlement can hardly be seen as a durable solution to climate-related displacement as long as key principles are not respected.